2009
DOI: 10.1124/jpet.108.148718
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic Acid Improves Imbalance between Vasodilator and Vasoconstrictor Actions of Endothelium-Derived Factors in Mesenteric Arteries from Rats at Chronic Stage of Type 2 Diabetes

Abstract: Accumulating evidence demonstrates that dietary intake of n-3 polyunsaturated fatty acids (PUFAs) is associated with a reduced incidence of several cardiovascular diseases that involve endothelial dysfunction. However, the molecular mechanism remains unclear. We previously reported that mesenteric arteries from type 2 diabetic Otsuka Long-Evans Tokushima fatty (OLETF) rats exhibit endothelial dysfunction, leading to an imbalance between endothelium-derived vasodilators [namely, nitric oxide (NO) and endotheliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 42 publications
4
85
1
1
Order By: Relevance
“…Both EPA and DHA increased 3-series prostacyclin production by endothelial cells to the same extent without affecting 2-series prostacyclin levels, suggesting a retroconversion from DHA to EPA (124) . In addition, EPA was shown to increase acetylcholine-induced endothelium-dependent hyperpolarising factor-mediated vasodilation in diabetic rats (125) . Endothelium-independent vasodilatory effects are mediated by the modulation of Ca 2 + signalling in smooth muscle cells, but the mechanisms, especially with respect to the type of Ca channels involved, remain uncertain (126)(127)(128)(129) .…”
Section: Arterial Compliancementioning
confidence: 99%
“…Both EPA and DHA increased 3-series prostacyclin production by endothelial cells to the same extent without affecting 2-series prostacyclin levels, suggesting a retroconversion from DHA to EPA (124) . In addition, EPA was shown to increase acetylcholine-induced endothelium-dependent hyperpolarising factor-mediated vasodilation in diabetic rats (125) . Endothelium-independent vasodilatory effects are mediated by the modulation of Ca 2 + signalling in smooth muscle cells, but the mechanisms, especially with respect to the type of Ca channels involved, remain uncertain (126)(127)(128)(129) .…”
Section: Arterial Compliancementioning
confidence: 99%
“…[25][26][27] Blood glucose was measured by a glucose meter (OneTouch Ultra, LifeScan, Johnson & Johnson Company, Milpitas, CA, U.S.A.). Plasma lipid parameters and plasma insulin were measured using commercially available kits (Wako Pure Chemical Industries, Ltd., Osaka, Japan and Shibayagi, Gunma, Japan, respectively).…”
Section: Measurement Of Blood Parameters and Blood Pressurementioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16]27,28) Plasma samples were stored at −20°C until analysis. Briefly, plasma glucose, cholesterol, high-density lipoprotein (HDL) cholesterol, triglyceride, and serum non-esterified fatty acid (NEFA) levels were each determined with a commercially available enzyme kit (Wako Pure Chemical Industries, Ltd., Osaka, Japan).…”
Section: Ca Mo and Rv Treatmentsmentioning
confidence: 99%
“…The endothelium plays a central role in physiological maintenance of the vascular function by regulating vascular tone, leukocyte adhesion, and platelet activation, as a result of the release of vasoactive substances such as nitric oxide (NO), prostacyclin, and thromboxane A 2 (TXA 2 ). 1,[6][7][8][9][10][11][12][13][14][15][16] Several natural polyphenols have been evaluated for their ability to protect against endothelial dysfunction and, thus, for their effectiveness in preventing cardiovascular disease. 17) Indeed, we have also shown that long-term chlorogenic acid (CA) treatment (2 months) can normalize the impaired endothelium-dependent relaxation seen in diabetic rats.…”
mentioning
confidence: 99%